Formulation and sensitivity analysis of a nonhydrostatic, axisymmetric tropical cyclone model - Hausman, Scott A., author; Schubert, Wayne, advisor; Montgomery, Michael T., committee member; Cotton, William R., committee member; Johnson, Richard H., committee member; McGinley, John A., committee member; Taylor, Gerald D., committee member (Colorado State University. Libraries, 2001)
To better understand the processes limiting tropical cyclone intensity, we simulate a symmetric tropical cyclone-like vortex using a two-dimensional model of a precipitating atmosphere. The model physics is derived from the unique equilibrium thermodynamics and nonhydrostatic primitive dynamics formulated by Ooyama. In addition, we generalize Ertel's potential vorticity (PV) principle to a precipitating atmosphere, expressing the resulting moist PV in terms of a virtual potential temperature that is a function of the total pressure and total density, including condensate. The distribution of moist PV is exactly invertible and similar to the dry PV distribution. Control and sensitivity experiments reveal that the simulated tropical cyclone is sensitive to the horizontal grid resolution, the ice and precipitation microphysics, and the horizontal diffusion. Most importantly, we reproduce the frontal collapse of the eyewall theorized by Emanuel and demonstrate indirectly that the moist PV structure is barotropically unstable. In addition, we find that the mesoscale downdraft outside the primary eyewall inhibits the inflow of entropy and absolute angular momentum into the storm core, weakening the tropical cyclone. Finally, we speculate that the intensity is indirectly linked to radiation, which drives the subsident drying necessary to maintain the moisture budget of the boundary layer against surface evaporation.
Keywords: atmosphere